2020
DOI: 10.3390/sports8090123
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Critical Power, the Work Capacity above Critical Power (W′), and Its Reconstitution: A Narrative Review of Current Evidence and Implications for Cycling Training Prescription

Abstract: The two-parameter critical power (CP) model is a robust mathematical interpretation of the power–duration relationship, with CP being the rate associated with the maximal aerobic steady state, and W′ the fixed amount of tolerable work above CP available without any recovery. The aim of this narrative review is to describe the CP concept and the methodologies used to assess it, and to summarize the research applying it to intermittent cycle training techniques. CP and W′ are traditionally assessed using a numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 141 publications
(262 reference statements)
0
23
0
Order By: Relevance
“…The observations from this study showed frequent bouts with various degrees of W' expenditure ( Figures 1B , 4 ), tending to a lower degree of W' expended in later rounds ( Figure 4 ; Table 2 ). The mechanisms, and even the descriptive kinetics, of W' recovery are still to be clarified, but possibly reflect a complex interplay of biochemical pathways, including restoration of blood and muscle oxygen stores, high-energy phosphates, and the ability to proceed with anaerobic glycolysis ( Miura et al, 2000 ; Jones et al, 2010 ; Chidnok et al, 2013 ; Chorley and Lamb, 2020 ). Recent evidence points toward a bi-phasic recovery, enabling rapid recovery of one fraction of W ', followed by a slower recovery of the remaining fraction ( Caen et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The observations from this study showed frequent bouts with various degrees of W' expenditure ( Figures 1B , 4 ), tending to a lower degree of W' expended in later rounds ( Figure 4 ; Table 2 ). The mechanisms, and even the descriptive kinetics, of W' recovery are still to be clarified, but possibly reflect a complex interplay of biochemical pathways, including restoration of blood and muscle oxygen stores, high-energy phosphates, and the ability to proceed with anaerobic glycolysis ( Miura et al, 2000 ; Jones et al, 2010 ; Chidnok et al, 2013 ; Chorley and Lamb, 2020 ). Recent evidence points toward a bi-phasic recovery, enabling rapid recovery of one fraction of W ', followed by a slower recovery of the remaining fraction ( Caen et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…An incremental cycling test to exhaustion performed one week before was employed to assess training status of participants and determine each volunteer’s critical power to quantify the individualised training load. Previous studies showed a good correlation between power output at the respiratory compensation point or ventilatory threshold 2 (WVT2) and the critical power [ 15 , 16 , 17 ], which demarcate the heavy from severe exercise intensity domains. Methods, equipment and repeatability measures were the same as described elsewhere [ 18 ], but fixing was without wheels, pedalling always with road cycling shoes, and the incremental ramp test consisted of a 4 min warm-up at 100 W, followed by ramp test with 5 W increments every 12 s (25 W per minute).…”
Section: Methodsmentioning
confidence: 99%
“…The CP models are considered simple, robust, and promising [ 20 , 24 ]. The parameters ( CP and W′ ) are presumed to be associated with physiological responses to exercise [ 20 , 25 , 26 , 27 ]. On the other hand, the CP concept is also widely criticized and referred to as a purely mathematical artifact with very few practical applications [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the CP concept is also widely criticized and referred to as a purely mathematical artifact with very few practical applications [ 28 , 29 ]. The Skiba model is yet to be adopted by endurance coaches [ 25 ]. The W′ reconstitution requires further work and individual adjustments [ 19 , 25 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation